Impact of perioperative immunonutrition on postoperative outcomes in pancreaticoduodenectomy: a systematic review and meta-analysis of randomized controlled trials - Gaofeng Zhang; Bing Zhao; Tengang Deng; Xiaofei He; Yongpin Chen; Changtao Zhong; Jie Chen (BMC Gastroenterology)
Abstract Background This systematic review and meta-analysis aimed to evaluate the impact of perioperative immunonutrition on postoperative outcomes in patients undergoing pancreaticoduodenectomy (PD). Methods Conducted a comprehensive search in PubMed, Embase, Cochrane Library, Medline, and Web of Science databases to identify all randomized controlled trials (RCTs) on the topic of immunonutrition and PD. Subsequently screened literature, extracted data, and assessed the risk of bias in the included studies, and finally conducted a meta-analysis using RevMan 5.3 software. Results The analysis included a total of 10 RCTs with 574 patients, among whom 288 were in the immunonutrition group and 283 in the control group. The meta-analysis revealed a significantly lower incidence of postoperative infection-related complications (OR = 0.45; 95% CI: 0.27–0.74; P = 0.002) and severe postoperative complications (OR = 0.61; 95% CI: 0.38–0.98; P = 0.04) in the immunonutrition group compared to the control group. Additionally, patients in the immunonutrition group had a significantly shorter length of hospital stay (MD= -1.87; 95%CI -3.29 - -0.44; P = 0.01). However, the analysis revealed no statistically significant difference in the overall complication rate between the two groups (P = 0.67). Furthermore, the incidence of specific complications and perioperative mortality rates also did not demonstrate any statistically significant differences (all P > 0.05). Conclusions Perioperative immunonutrition in PD patients can reduce postoperative infection-related complications, but more high-quality RCTs are needed for further validation.